Maternal Knowledge and Feeding Practices Associated with Childhood Stunting in Rural Indonesia: A Case Control Study - Elin Mutia Sari; Nur Alam Fajar; Rizma Adlia Syakurah; Kiki Sulaningsi; Esti Sri Ananingsih; Risa Nur Amalia; Sinta Octaviana (Jurnal Ilmu Kesehatan Masyarakat, 2026)
Childhood stunting remains a major public health problem in rural Indonesia, where inadequate maternal nutrition knowledge and suboptimal child feeding practices are prevalent. A case–control study was conducted among 210 mothers of children aged 24–59 months in Banyuasin Regency, South Sumatra, including 105 stunted and 105 non-stunted children. Data were collected through face-to-face interviews using validated questionnaires to assess maternal nutrition knowledge and supplementary feeding practices. Multivariate logistic regression analysis was performed to estimate adjusted odds ratios (AOR) and 95% confidence intervals (CI). Children whose mothers had good nutrition knowledge were less likely to be stunted (AOR = 0.458; 95% CI: 0.250–0.838; p = 0.014). Similarly, appropriate supplementary feeding practices were associated with lower odds of stunting (AOR = 0.486; 95% CI: 0.266–0.885; p = 0.019). Child’s sex and birth weight were not significantly associated with stunting. Maternal nutrition knowledge and appropriate feeding practices were independently associated with lower odds of childhood stunting in rural Indonesia. Strengthening maternal education and feeding support may contribute to effort to reduce stunting in rural settings.